An audit of rehabilitation input for patients with brain and spinal tumour within the Greater MancheSTER. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Robson, Sara; Emerson, Julie; Connor, Neil
Abstract : Background: In 2008, the National Cancer Action team started a cancer rehabilitation workforce scoping exercise. As a result of this, eight cancer disease group rehabilitation pathways and four symptom specific pathways were published in 2010. The pathways were written following all available evidence and examples of best practice, where evidence was not available. (National Cancer Action Team; Briefing Paper 2 CRWP September 2008) As part of our role we were given the task of introducing the Brain and CNS rehab pathway to our local cancer network (Greater Manchester and Cheshire Cancer Network). We were required to localise the pathway and examine how closely the rehab provided for the brain and CNS tumour patients was following the suggested 'best practice' in the rehab pathway. We had assistance of the local Supra District Audit office to audit the existing pathway and rehabilitation interventions prior to our input, and re audit following a year of education and promotion of the pathway. Aim of the presentation: The aim of the poster is to detail the processes that led to the production of a successful audit tool, and to discuss the 'trials and tribulations' of carrying out a regional audit of patient notes which spanned numerous separate agencies. We aim to make others aware of some of the pitfalls surrounding multi agency audit. Methodology: A retrospective audit of medical/allied health professional notes was carried out on a sample of randomly selected patients diagnosed with a primary brain or spinal tumour within a specified period. All agencies involved have been made aware of the audit and each individual Information Governance Team has had to give approval. As the audit did not involve discussion with patients, ethical approval was not required.